2004
DOI: 10.1001/archderm.140.5.563
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Activity of Melaleuca alternifolia (Tea Tree) Oil

Abstract: Tea Tree oil (TTO) contains beneficial properties such as antibacterial, antimicrobial, antiviral and anti-fungal. Whereas, the medium chain fatty acids in Virgin Coconut oil (VCO) able to protect hair follicles from heat, restoring hair's moisture and other damage. This paper describes the physical properties of seven hair shampoo formulations containing differing amount of TTO and VCO. The essential oils (TTO) applied in these formulations were extracted from fresh tea trees using steam distillation method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(53 citation statements)
references
References 39 publications
2
46
2
1
Order By: Relevance
“…In another study, clove oil also showed toxicity against house dust mite Dermatophagoides pteronyssinus [27]. The lethal time of 5% tea tree oil was reported 180 min [18], whereas in our investigation, all mites died after 90 and 30 min of exposure to 5 and 10% tea tree oil, respectively. Furthermore, our findings showed no scabicidal effect with cade oil which was previously demonstrated effective against head lice and poultry red mites [14, 28].…”
Section: Discussioncontrasting
confidence: 41%
“…In another study, clove oil also showed toxicity against house dust mite Dermatophagoides pteronyssinus [27]. The lethal time of 5% tea tree oil was reported 180 min [18], whereas in our investigation, all mites died after 90 and 30 min of exposure to 5 and 10% tea tree oil, respectively. Furthermore, our findings showed no scabicidal effect with cade oil which was previously demonstrated effective against head lice and poultry red mites [14, 28].…”
Section: Discussioncontrasting
confidence: 41%
“…We have previously investigated the acaricidal activity of natural product extracts of tea-tree oil and clove oil and their active components using in vitro studies of mites collected from pigs with experimental scabies infestation [5]. These studies have shown potential useful acaricidal activity of essential oils- tea-tree ( Melaleuca alternifola ) and clove ( Eugenia caryophyllata ), and their active components [6,7]. …”
Section: Resultsmentioning
confidence: 99%
“…Local policies encourage the hospitalization of patients with crusted scabies for clinical management, as well as environmental health input to address the risk of ongoing transmission in an index patient's household. The standard treatment protocol for crusted scabies includes prolonged hospitalization in a single room with contact precautions, the use of topical benzyl benzoate plus 5% tea tree oil 2–3 times per week [14], multiple doses of oral ivermectin (as described below), topical keratolytics, systemic antibacterial drugs where judged clinically necessary, and attention to medical comorbidities.…”
Section: Methodsmentioning
confidence: 99%